The Concept and Operational Aspect of Takaful: Practices and Issues - Isa, Mohamad Yazid; Mohamed Naim, Asmadi; Abdul Rahim, Ahmad Khilmy (2018)
Even though the development of takaful industry is very encouraging and variety of takaful models have been implemented, but the industry faces a lot of issues and challenges especially in the Shariah and operational matters. This paper discusses the current development of takaful industry in Malaysia and highlights the major issues and challenges in developing a resilient takaful market. Interviews with several experts from the takaful industry and academician from several universities have been conducted to study their views on the discussed matters. This paper found that the major issues in existing takaful models derived from juristic difference among scholars. There are also efforts taken by several parties to harmonize these by going back to the basic of takaful which are brotherhood and mutual assistant